ON THE REPLACEMENT OF VOLUNTARY VOTING FOR MANDATORY VOTING IN THE REPUBLIC OF CHILE - E. P. Marmilova (Современная наука и инновации, 2022)
The author of the article is considering replacing voluntary voting with mandatory voting in the Republic of Chile in 2020.